Effects of Electroacupuncture at Different Acupoints on Functional Dyspepsia Rats. (1st February 2022) - Li, Yue-Jie; Yang, Na-Na; Huang, Jin; Lin, Lu-Lu; Qi, Ling-Yu; Ma, Si-Ming; Hu, Cheng-Xin; Wang, Yu; Yang, Jing-Wen; Liu, Cun-Zhi
Abstract : Although, acupoint specificity is regarded as the core of scientific issues in electroacupuncture (EA), the difference of EA on treating functional dyspepsia (FD) at different acupoints is unclear. Therefore, this study aims to investigate the different therapeutic effects of EA at lower extremity or abdominal acupoints on the mucosal integrity and lower-inflammatory response in FD. The intragastric administration of iodoacetamide (IA) was performed in 48 rats to establish the FD model. These rats were randomly divided into the control group, the model group and the six EA groups receiving stimulation at the lower extremity (ST36, ST37, and ST39) or abdominal acupoints (ST25, CV4, and CV12) separately. The open-field test (OFT) was measured after 8 weeks of IA, and gastric emptying was evaluated after 10 days of the EA treatment. The local inflammation markers of CD45, eosinophil major basic protein (EMBP), and the tight junction proteins ZO1 and Claudin3 were assessed by immunofluorescence in all groups. Western blot analysis showed that the EMBP and Occludin1 levels in the duodenal. EA at lower extremity acupoint ST36 could improve the gastric emptying. EA at lower extremity acupoints reduced the immunoreactivity of EMBP, but the CD45 was reregulated by the ST37 and ST39 acupoints. The lower extremity acupoints also ameliorated FD-tight junction protein in the expression of Claudin3 and ZO1. However, only the ST36 suppressed the expression of EMBP and recovered the expression of Occludin1. Similarly, the effect of EA at abdominal acupoints was not obvious either in facilitating gastric motility or in improving inflammatory and mucosal injury. EA at lower extremity and abdominal acupoints with the same stimulation parameters had different therapeutic effects in gastric emptying, intestinal mucosal integrity, and inflammation response, thus proving the specificity of acupoints.